Bones of the lost [large type] : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2013)
While examining a bundle of Peruvian dog mummies confiscated by U.S. Customs, forensic anthropologist Tempe Brennan finds herself in the center of a human trafficking conspiracy when she investigates the murder of a teenage girl.